Analisis Kebijakan Struktur Modal, Manajemen Laba, Dan Kepemilikan Publik Terhadap Financial Distress: Studi Empiris Pada Industri Makanan Dan Minuman di Indonesia - Murti, Pertiwi Harkitianis; Zamzamy, Faizal Ridwan; Maharani, Novita Kusuma (Robust: Research of Business and Economics Studies, 2024)
This research aims to determine the influence of capital structure, earnings management and public ownership on financial distress in the food and beverage industry in Indonesia, which is proxied by the Deb to Equity Ratio, Working Capital Accrual to Period Income, Total Public Shares to Outstanding Shares. This research uses secondary data obtained through documentation in the form of annual financial reports from food and beverage industry companies in Indonesia. Data analysis was carried out using quantitative analysis in the form of descriptive statistical tests, normality tests, and hypothesis testing with paired sample tests. The research results show that Capital Structure, Profit Management and Public Ownership have an influence and significance.